Analysis of Zakat Fundraising Strategies Through E-Commerce Platform in Increasing Revenue at Initiative Zakat Indonesia - Nur Annisa Fitri; Ach .Yasin (Edumaspul: Jurnal Pendidikan, 2023)
Indonesia is a country with the largest Muslim population with 86.88% of the total population of Indonesia being Muslim. (kemendagri.go.id, 2021). In Islamic teachings there is the term zakat, which is an obligation in the Islamic faith to pay a certain portion of some wealth. Based on the Zakat Outlook 2017 in PUZKAS BAZNAS that the potential for zakat in Indonesia reaches 217 T while the accumulated potential is only 5 T. Advances in payment system technology can replace the role of cash as a more effective non-cash payment instrument and efficiently, e-commerce has become the choice for the fundraising strategy implemented by the Initiative Zakat Indonesia. This research aims to find out how the zakat fundraising strategy through the e-commerce platform at the Initiative Zakat Indonesia institution can maximize the existing zakat potential. This research is qualitative research and uses descriptive qualitative methods. In this study, the subject-taking technique used targeted sampling and interview data collection techniques, and data source triangulation was used as data validity. The results of this study state that the Zakat collection strategy through the Initiative Zakat Indonesia Institution's e-commerce platform has been quite successful in maximizing the potential of Zakat